LEVEL OF SUBJECTIVE PERCEPTION OF THE MUSCLE SORENESS OF A DOUBLE FEMALE VOLLEYBALL AFTER TWO TYPES OF RECOVERY INTERVAL - Marques , Nelson; Oliveira , Alba (Revista Inclusiones, 2016)
The objective of the study was to detect a type of interval – active or passive, that reduces more the subjective perception (SP) of the muscle soreness. The sample was composed by a double female volleyball that competed in three competitions of the Brazilian Circuit 2015/2016. The face scale of the SP of the muscle soreness of the physical effort of the volleyball was presented before and after the games. The face scale of SP effort adapted of Foster and SP difficulty scale of the opponent were presented after the game. The protocol of the active aerobic interval used in the qualifying and in the 4th phase followed the following guidelines: intermittent effort (light run and walk) in the distance of 10 meters with a stimulus of 3 minutes. The intensity of the active interval was monitored by the talk test (level 1 = comfortable speak). But in the 5th phase of the Brazilian Circuit occurred the passive interval. Friedman Anova did not detect significant difference in the internal load of the game of each championship, X2 (2) = 6, p = 0,06. Friedman Anova did not detect significant difference SP difficulty scale difference of the opponent of each championship, X2 (2) = 6,1, p = 0,06. Friedman Anova did not detect significant difference SP of the muscle soreness various moments of the different competitions, X2 (18) = 28,14, p = 0,06. In conclusion, the active aerobic interval seems to decrease the SP of the muscle soreness.